Transgenic models in pharmacology - Offermanns, Stefan; Hein, Lutz (Springer, 2004)
The aim of this volume is to give up-to-date information on animal models generated by transgenic or gene targeting techniques. Naturally, the focus is on the mouse system. Each chapter has been written by leading experts in the field and gives an overview on existing animal models. This is facilitated by tables, which list the most important genetically engineered animal models and their phenotypes. This book aims at illustrating the impact of transgenic animal models in the field of Experimental Pharmacology and Toxicology, which includes their role in the understanding of basic cellular mechanisms, the evaluation of potential drug targets or the testing for drug effects
Keywords: Aufsatzsammlung; Tiermodell; Transgene Tiere; Arzneimittelforschung